Decolonising theorising on children: Moving towards African-centred childhood studies pedagogy of sexual violence and trauma - Titi, N. (South African Journal of Higher Education, 2023)
Background: In Africa, remnants of colonisation and the effects of coloniality have influenced childhood in ways dissimilar to those in other parts of the world. Objectives: This article contests against universalised theorising of children, advocates for Afrocentric approaches to childhood studies on African children, and makes a case for Afrocentric pedagogy in the psychology of child sexual violence and childhood trauma. Methodology: The arguments in this article are informed by a rapid review of doctoral research on the history of violence in South Africa and developmental theory to understand how children make meaning of the experience of sexual violence-related trauma. Results: South Africa’s history of colonisation and Apartheid significantly contributes to child outcomes. Decolonial thought and African-centered theorising must be applied to childhood studies in Africa for a contextual understanding of African childhoods. They must centre on the needs and worldviews of Africans. Conclusion: Education is an instrument of enculturation; therefore, pedagogy should reflect the people it studies. The methods and practice in teaching childhood studies in psychology in Africa must humanise both children and professionals. Contribution: The article addresses the questions of relevance in childhood studies in Africa and advances recommendations for how academics and practitioners in childhood sexual violence and psychology should work with complex knowledge in childhood studies pedagogy.